Assesing TM'S internet services in Johor: consumer & organizational analysis / Ainazura Kasim, Azlan Ibrahim, & Mazliha Jumahat - Kasim, Ainazura; Ibrahim, Azlan; Jumahat, Mazliha (2012)
Telecommunication industry is changing rapidly. Along the way, the volatility in nature of communication industry has impacted they way people communicate in the modern days. Three decades ago, no one would have thought that Internet and broadband will be the most prominent communication means in the digital age. Years goes by, the adoption rate of internet is increasing due to the emerging awareness on the importance of this cutting edge telecommunication channel. Moving in tandem with the emerging the broadband facilities also are enhanced by many providers these days. Telekom Malaysia is Malaysia's leading broadband provider in the country for provider the fixed broadband companies via Streamyx and Unifi. The study is assessing on TM as the Telco that provides broadband services to users in this country. The coverage of this study is covering on the analysis on internet users in Johor to determine their action level on broadband facilities at the state. At the same time, we are looking into TM's International Analysis that revolves around its internal and external factors in the light of the Strengths, Weaknesses, Opportunities and Threats. In completing our assessment in this study, we have conducted. The industry analysis to study on the nature of telecommunication industry in the light of market entry, Competition, product substitution, buyers' purchasing powers, and power of suppliers. Conclusion has been determined after integrating the analyses of all the assessments. TM is operating an industry that is volatile in nature which requires continuous improvement initiatives to stay relevant in the industry. As the competition for TM is going to be enhanced due to the emerging open policy by the government, TM has to come out with value differentiation initiative to create competitive edge in the effort to make the competitors irrelevant to this Telco.